Can NGOs regulate medicines markets? Social enterprise in wholesaling, and access to essential medicines - Chaudhuri Sudip; Mackintosh Maureen; Mujinja Phares GM (BMC, 2011)
Abstract Background Citizens of high income countries rely on highly regulated medicines markets. However low income countries' impoverished populations generally struggle for access to essential medicines through out-of-pocket purchase on poorly regulated markets; results include ill health, drug resistance and further impoverishment. While the role of health facilities owned by non-governmental organisations (NGOs) in low income countries is well documented, national and international wholesaling of essential medicines by NGOs is largely unstudied. This article describes and assesses the activity of NGOs and social enterprise in essential medicines wholesaling. Methods The article is based on a set of interviews conducted in 2006-8 with trading NGOs and social enterprises operating in Europe, India and Tanzania. The analysis applies socio-legal and economic perspectives on social enterprise and market regulation. Results Trading NGOs can resist the perverse incentives inherent in medicines wholesaling and improve access to essential medicines; they can also, in definable circumstances, exercise a broader regulatory influence over their markets by influencing the behaviour of competitors. We explore reasons for success and failure of social enterprise in essential medicines wholesaling, including commercial manufacturers' market response; social enterprise traders' own market strategies; and patterns of market advantage, market segmentation and subsidy generated by donors. Conclusions We conclude that, in the absence of effective governmental activity and regulation, social enterprise wholesaling can improve access to good quality essential medicines. This role should be valued and where appropriate supported in international health policy design. NGO regulatory impact can complement but should not replace state action.